Legal Liability Of E-Commerce Platforms For Consumer Losses Resulting From Defective Products - Rian Darmawan Putra; Suparwi Suparwi; Firstnandiar Glica Aini (IHSA Institute, 2025)
This study examines the legal responsibility of e-commerce platforms for consumer losses resulting from defective products in electronic transactions. The concept of consumer loss is explored through the Consumer Protection Law (UUPK), the Electronic Information and Transactions Law (UU ITE), and the Government Regulation on Electronic System Operators (PP PMSE), which reveal normative gaps related to the role of digital platforms. The research identifies an optimal liability model, including business entity verification, system oversight, and dispute resolution mechanisms, in line with the EU Digital Services Act. These findings emphasize the need for regulatory harmonization and strengthening of platform obligations for effective consumer protection